2015
DOI: 10.1186/s12879-015-1333-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of children hospitalized with influenza A and B infections during the 2012–2013 influenza season in Italy

Abstract: BackgroundInfluenza is a major public health issue worldwide. It is characterized by episodes of infection that involve hundreds of millions of people each year. Since that in the seasons 2010–2011 and 2011–2012 the circulation of FLUB was decreasing we evaluated the clinical presentation, demographic characteristics, admitting department, and length of stay in children who contracted influenza admitted to Bambino Gesù Children’s Hospital, during the 2012–2013 influenza season, with the aim to establish if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 20 publications
10
37
2
5
Order By: Relevance
“…The circulating FLU-A strains have changed in composition and this may have an effect on the clinical presentation of FLU nowadays. A recent study showed a more severe disease course in children with FLU-A compared to FLU-B [28]. The DSS for HBoV was high in our study.…”
Section: Single Infectionssupporting
confidence: 43%
“…The circulating FLU-A strains have changed in composition and this may have an effect on the clinical presentation of FLU nowadays. A recent study showed a more severe disease course in children with FLU-A compared to FLU-B [28]. The DSS for HBoV was high in our study.…”
Section: Single Infectionssupporting
confidence: 43%
“…Concerning the frequency of complications and underlying conditions (Table ), we also found very few significant differences between the influenza viruses in the unadjusted virus comparisons. There was some evidence that A(H1N1)p may result in more complications compared to other influenza virus (sub)types: People infected with A(H1N1)p more often had pneumonia and were more frequently admitted in the ICU compared to influenza B, and more frequently had upper respiratory tract infections, pneumonia, and ICU admissions compared to A(H3N2).…”
Section: Resultsmentioning
confidence: 66%
“…The assessment of the unadjusted differences in the frequency of symptoms and signs (Table and Table ) also showed few differences between the influenza viruses. Compared to influenza B, there was some evidence that patients with influenza A (not further specified) less often presented with myalgia (four studies—all focusing on children—of fifteen) were less often sent to the hospital for medical advice and/or further investigation (two studies of fourteen) and more often presented with cough (two studies of nine).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In a study by Mancinelli et al a total of 133 respiratory specimens positive for the influenza A and B viruses were subtyped during the 2012-2013 influenza season in Italy. Influenza B was slightly more prevalent (53.38%) than influenza A (46.62%) and the most common subtype was A/H1N1 (87.1%) while only 12.9% were A/H3N2 [26].…”
Section: Discussionmentioning
confidence: 96%